2011
DOI: 10.3402/qhw.v6i1.5917
|View full text |Cite
|
Sign up to set email alerts
|

Hope in action—facing cardiac death: A qualitative study of patients with life-threatening disease

Abstract: Coping with existential challenges is important when struck by serious disease, but apart from cancer and palliative care little is known about how patients deal with such issues and maintain hope. To explore how patients with life-threatening heart disease experience hope when coping with mortality and other existential challenges, we conducted a qualitative study with semi-structured interviews. We made a purposive sample of 11 participants (26–88 years) who had experienced life-threatening disease: eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
2
24
0
1
Order By: Relevance
“…They found that hope could enhance and diminish existential distress and was described in the four themes: Perceiving the realities of death—between overwhelming horror and peaceful acceptance ; Adapting to a new phase in life—between reconciliation and uncertainty ; Identity as seriously ill—between go‐ahead spirit and resignation; and lastly, The impact of relationship—between support and concern . Their study reported that to be cared for by skilled personnel and hear the physicians say that they should together act and make it all turn out well, provided patients with hope (Schaufel et al., ). This is consistent with our findings where it was obvious that hope was created when patients felt respected and they participated in the treatment and when they trusted the doctors.…”
Section: Discussionmentioning
confidence: 99%
“…They found that hope could enhance and diminish existential distress and was described in the four themes: Perceiving the realities of death—between overwhelming horror and peaceful acceptance ; Adapting to a new phase in life—between reconciliation and uncertainty ; Identity as seriously ill—between go‐ahead spirit and resignation; and lastly, The impact of relationship—between support and concern . Their study reported that to be cared for by skilled personnel and hear the physicians say that they should together act and make it all turn out well, provided patients with hope (Schaufel et al., ). This is consistent with our findings where it was obvious that hope was created when patients felt respected and they participated in the treatment and when they trusted the doctors.…”
Section: Discussionmentioning
confidence: 99%
“…This attitude was also described by people living with life-threatening diseases, who said that dying from an MI was considered a good way to go, like turning off the switch. 29 A person's narrative automatically includes the present, the past, and the future. When describing the present, the person relates events to what has been and what is about to come.…”
Section: Comprehensive Understanding and Reflectionsmentioning
confidence: 99%
“…High levels of enterprise block tendencies for resignation and submissiveness in the face of adversity and instead reflect the desire to continue. Among patients presenting chronic heart disease, an enterprising outlook seems essential to satisfactory prognosis [16].…”
Section: Introductionmentioning
confidence: 99%